Chronic NKG2D Engagement In Vivo Differentially Impacts NK Cell Responsiveness by Activating NK Receptors - Koch, Christine; Kim, Younghoon; Zöller, Tobias; Born, Christina; Steinle, Alexander (Frontiers in Immunology, 2017)
Immunosuppression is a typical hallmark of cancer and frequently includes perturbations of the NKG2D tumor recognition system as well as impaired signaling by other activating NK cell receptors. Several in vitro studies suggested that sustained engagement of the NKG2D receptor, as it is occurring in the tumor microenvironment, not only impairs expression and function of NKG2D, but also impacts signaling by other activating NK receptors. Here we made use of a transgenic mouse model of ubiquitous NKG2D ligand expression (H2-Kb-MICA mice) to investigate consequences of chronic NKG2D engagement in vivo for functional responsiveness by other activating NK receptors such as NKp46 and Ly49D. Unexpectedly, we found no evidence for an impairment of NKp46 expression and function in H2-Kb-MICA mice, as anticipated from previous in vitro experiments. However, we observed a marked down-regulation and dysfunction of the activating receptor Ly49D in activated NK cells from H2-Kb-MICA mice. Ly49D shares the adaptor proteins DAP10 and DAP12 with NKG2D possibly explaining the collateral impairment of Ly49D function in situations of chronic NKG2D engagement. Altogether, our results demonstrate that persistent engagement of NKG2D in vivo, as often observed in tumors, can selectively impair functions of unrelated NK receptors and thereby compromise NK responsiveness to third-party antigens.